The Influence of Internal and External Factors on Stock Returns in the Transportation Sub-Sector Listed on the Indonesia Stock Exchange in 2021–2023 - Sumiyati Sumiyati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The objective of this study is to examine the impact of internal and external factors on stock returns of companies in the transportation, logistics, and delivery sectors listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. This research employs a quantitative methodology, and the data were analyzed using SPSS version 27. The findings from the simultaneous regression analysis indicate that four independent variables, Return on Assets (ROA), Debt to Equity Ratio (DER), Return on Equity (ROE), and inflation, jointly have a statistically significant effect on stock returns (Sig. = 0.044 < 0.05). However, the results of the partial (individual) test reveal that only the inflation variable has a statistically significant influence, and the relationship is negative. This suggests that an increase in inflation tends to reduce stock returns.